Antiretroviral resistance and genetic diversity of human immunodeficiency virus type 1 isolates from the Federal District, Central Brazil - Cerqueira, Daniela M (2004)
In the context of universal access to antiretroviral therapy, the surveillance of human immunodeficiency virus type 1 (HIV-1) genetic diversity and resistance becomes pivotal. In this work our purpose was to describe the genetic variability; prevalence of drug-resistance mutations; and genotypic resistance profiles in HIV-1 infected individuals under antiretroviral treatment, from the Federal District, Brasília, Central Brazil. The entire viral protease and codons 19 to 234 of the reverse transcriptase gene from 45 HIV-1 isolates were amplified and sequenced for subtyping and genotyping. By phylogenetic analysis, 96% of the samples clustered with subtype B and the remaining 4% with HIV-1 subtype F sequences. One major protease inhibitor resistance-associated mutation, I50V, was detected in 38% of the samples. Minor mutations were also found at the protease gene: L10I/V (7%), K20M (2%), M36I (11%), L63P (20%), A71T (2%), and V77I (7%). Many mutations associated with reduced susceptibility to nucleoside or non-nucleoside reverse transcriptase inhibitors were detected: M41L (11%), E44D (4%), D67N (11%), T69D (2%), K70R (11%), L74V (2%), L100I (4%), K103N (18%), V118I (9%), Y181C (11%), M184V (18%), G190A (4%), T215Y (4%), and K219E (4%). This study has shown that 84% of the studied population from the Federal District, showing evidences of therapy failure, presented viral genomic mutations associated with drug resistance. The main antiretrovirals to which this population showed resistance were the PI amprenavir (38%), the NNRTIs delavirdine, nevirapine (31%), and efavirenz (24%), and the NRTIs lamivudine (18%), abacavir, and zidovudine (13%).